2023
DOI: 10.3389/fnagi.2023.1106497
|View full text |Cite
|
Sign up to set email alerts
|

Signature of miRNAs derived from the circulating exosomes of patients with amyotrophic lateral sclerosis

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a progressive, fatal neurodegenerative disorder (NDS) with unclear pathophysiology and few therapeutic options. Mutations in SOD1 and C9orf72 are the most common in Asian and Caucasian patients with ALS, respectively. Aberrant (microRNAs) miRNAs found in patients with gene-mutated ALS may be involved in the pathogenesis of gene-specific ALS and sporadic ALS (SALS). The aim of this study was to screen for differentially expressed miRNAs from exosomes in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…However, the valuable information derived from our detailed computational analysis could be used for the identification of alternative biomarkers for diagnosis and/or prognosis. Indeed, it has recently been proposed that accurate expression profiling of disease-associated miRNAs (MDAs) combined with machine learning or deep learning strategies can serve as an innovative diagnostic tool for various physiological disorders in patients 64 , 65 , including certain types of sclerosis 66 , Lyssavirus infection 67 , and COVID-19 68 . Hence, this comprehensive study might provide, once the regulatory pathways involved in the sncRNA-mediated response are characterized, a new perspective for the development of innovative therapeutic and/or prophylactic strategies for the control and management of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the valuable information derived from our detailed computational analysis could be used for the identification of alternative biomarkers for diagnosis and/or prognosis. Indeed, it has recently been proposed that accurate expression profiling of disease-associated miRNAs (MDAs) combined with machine learning or deep learning strategies can serve as an innovative diagnostic tool for various physiological disorders in patients 64 , 65 , including certain types of sclerosis 66 , Lyssavirus infection 67 , and COVID-19 68 . Hence, this comprehensive study might provide, once the regulatory pathways involved in the sncRNA-mediated response are characterized, a new perspective for the development of innovative therapeutic and/or prophylactic strategies for the control and management of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…We identi ed and validated lnc-HIBADH-4 as one of the most signi cantly downregulated lncRNAs in ALS patients. Several miRNAs [14,18], including miR-181, have been found to be differentially expression in peripheral blood cells and may serve as novel biomarkers when combined with NfL [13]. Although several studies have investigated the mechanisms of lncRNAs in the pathogenesis of ALS, their potential as diagnostic and prognostic biomarkers remain unknown [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs could serve as diagnostic and prognostic biomarkers for ALS [13][14][15][16][17][18]. Also, AAVdelivered miRNAs could provide potential for a targeted therapy for ALS patients carrying SOD1 variant [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, due to the nature of EVs and their superior cargoes and stability in biofluids, EVs have garnered great interest in the non-invasive diagnosis of ALS [267][268][269][270][271][272]. When it comes to EVs as biomarkers for ALS, many researchers have focused on dysregulated miRNAs [273]. Banack et al confirmed previous studies reporting that miR-146a-5p is up-regulated while miR-4454 is down-regulated in the blood plasma-derived EVs of ALS patients compared to healthy controls [267].…”
Section: Other (Als and Hd)mentioning
confidence: 99%